Center-Pivot-Irrigated Alfalfa Cost-Return Budget (Custom Harvested) - O'Brien, Daniel M.; Sartwelle III, James D. (My University, 1997)
This publication projects a budget that reflects expected income and costs based on center-pivot-irrigated alfalfa production in Kansas.
MF584_1997_10
Keywords: MF584; Economics; Crops; MF